The use of aerobic bacteria to reduce organic pollutant in pulp industrial waste liquid - Isnauli Simatupang; M. Hasbi; Budijono ' (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2016)
The effectiveness of waste water treatment plant PT. Toba Pulp Lestari, Tbk in reducing organic pollutant (BOD, COD) content in liquid waste is relatively low as the number of decomposer bacteria is low. To increase the effectiveness of waste water treatment plant in reducing organic pollutant, aerobic bacteria addition is needed. To understand the effectiveness of the aerobic bacteria in reducing organic pollutant, a study has been conducted in December 2015. The aerobic bacteria was taken from the alkali sewer waste and it is used to reduce the organic pollutant in the waste was taken from deep tank aeration system. There were control (0L), 0.25L (P1), 0.5L (P2) and 0.75L (P3) of liquid waste that content of aerobic bacteria in 3L waste was taken from deep tank aeration system. The best result were obtained in P3, by the end of experiment, there was 83 mg/L of BOD and 86 mg/L of COD. All of the treated waste were then used to rear Cyprinus carpio and Oreochromis niloticus fingerlings for two days. Survival rate of the fish were 100%. Based on data obtained, it can be concluded that all of treated waste can be used for rearing the fish.Key Words: Aerobic bacteria, BOD, COD, pulp industrial waste liquid